INVESTIGATION OF ANTIOXIDANT POTENTIAL OF QUERCETIN AND HESPERIDIN: AN IN VITRO APPROACH - Priyanga K, Srimathi; K, Vijayalakshmi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The study was carried out to evaluate the antioxidant potential of quercetin and hesperidin. Methods: The antioxidant potential of quercetin and hesperidin was estimated using free radicals in in vitro condition. Antioxidant activity of quercetin and hesperidin was estimated using 1,1-diphenyl-2-picrylhydrazyl (DPPH), superoxide, nitric oxide, hydroxyl radical, hydrogen peroxide radical, and reducing power assay. Results: Quercetin and hesperidin have high efficiency in scavenging free radicals. Both the compounds are more efficient in scavenging DPPH (IC50 value 36.15±0.30 and 41.55±0.49 mg/ml) and superoxide radicals (IC 50 value 19.3±0.26 and 28.08 ±0.18 mg/ml) have high reducing capacity when compared to the standards ascorbic acid (IC50 value 31.45±1.31 and 23.2±0.20 mg/ml). Conclusion: The present study suggests that quercetin and hesperidin have significant antioxidant activities and could be easily accessible to the immune system.